Perbandingan Manajemen Berbasis Sekolah antara SMP Negeri I Diwek dan MTs Negeri Keras Diwek Jombang - Hanif Prasetyo; Khduriyah Khudriyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
This research pupose is to know the school based management implementation at SMP Negeri I Diwek and MTs Negeri Keras. The research uses qualitative approach. The data was collected using observation, interview, and documents as instrument. The result of this research showed that the school based management of both SMP Negeri I Diwek and MTs Negeri Keras by implementing five steps such as: (1) planning, included: situation analysis, formulating objectives and SWOT analysis, (2) implementation, (3) supervision, (4) evaluation, and (5). reporting. The target and gols can be achieved by supporting of various elements exist in the schools, adequate facilities, infrastructure, the work ethic and high morale of all elements. While the inhibiting factors of these two schools is not very meaningful, because both of them have done planning and consideration before the implementation of school-based management. Howeve, the facilities and infrastructure at MTs Negeri Keras is inadequate. The similarities between the two schools are able to implement school-based management properly, implement school and community relations, as well as carrying out monitoring and evaluation based on the ability of each school. The difference is in the form of a program that is implemented at both schools.